Restorative Justice for the Survivor of Sexual Violence - Aminah, Siti; Sugitanata, Arif; Karimullah, Suud Sarim (Restorative : Journal of Indonesian Probation and Parole System, 2024)
One type of gender-based violence is sexual violence. Instances of sexual violence manifest in diverse spheres of existence, encompassing both private and communal spheres. The perpetrators escaped pun- ishment. However, the victims were not provided with adequate assistance. This study seeks to offer a comprehensive analysis of the implementation of restorative justice, specifically focusing on its positive impact on the physical and psychological rehabilitation of victims of sexual violence. This study employs normative legal research methodology, focusing on statutory regulations and utilizing a conceptual approach. Various sources such as statutory regulations, journals, books, reports, and similar references are consulted. This study finds that achieving justice for survivors of sexual abuse is contingent upon the involvement of knowledgeable and trained individuals who possess expertise in the power dynamics and control mechanisms inherent in sexual violence, as well as a profound comprehension of the effects of trauma. In addition to that, the following factors must take precedence when implementing restora- tive justice for victims of sexual violence: Ensuring the protection of the victim, preventing the offender from manipulating the process, ensuring the victim is not under any pressure, avoiding conflicts of loy- alties, providing services that benefit the public, and maintaining a balance of power. [Kasus kekerasan seksual sudah menjadi salah satu bentuk kekerasan berbasis gender yang sangat sering menimpa kaum perempuan. Kasus kekerasan seksual terjadi di berbagai lini kehidupan, baik ranah domestik maupun ranah publik. Acapkali pelaku yang seharusnya dijerat hukum dan korban yang harusnya mendapat pelayanan tidak terlaksana dengan baik. Penelitian ini bertujuan untuk memberikan gambaran penerapan restorative justice yang pro terhadap pemulihan fisik dan psikol- ogis korban penyintas kekerasan seksual. Penelitian ini menyimpulkan bahwa keadilan terhadap korban penyintas kekerasan seksual dapat diterapkan jika berbagai pihak yang menangani adalah tenaga ahli yang telah ditraining terkait dinamika kekuasaan dan mekanisme kontrol yang terlibat dalam kekerasan seksual, serta pemahaman mendalam tentang dampak trauma. Selain itu, aspek- aspek berikut harus menjadi prioritas ketika menerapkan keadilan restoratif bagi korban kekerasan seksual: Menjamin keselamatan korban, menjamin pelaku tidak memanipulasi proses, korban tidak dalam tekanan, tidak adanya konflik kesetiaan, ketersediaan pelayanan terhadap kepentingan publik, dan keseimbangan kekuasaan.]